PENGARUH POLA PENGASUHAN TERHADAP KEMAMPUAN BERPIKIR KRITIS ANAK DALAM PEMBELAJARAN - Unita Sukma Zuliani Nasution (Jurnal Sintaksis, 2019)
Every parents has steps to take care of children. The steps and patterns will be different between one family with another family. The parenting to children is the mirror of behavior and attitude from the parents to their children in communcation and interaction. While the children has problem in the house, they have obstacle when they are studying in the school. A lack of concentration, feel depressed, cannot be able to make decision and cannot speak to tell his opinion will influence to students, especially the effectiveness in learning the lesson in the school. Therefore, the parenting of the parents in the house will make the personality of the children is better, especially in studying all of lesson that are given by the teacher in the school.